Leveraging long-acting IL-15 agonists for intratumoral delivery and enhanced antimetastatic activity - Hangasky, John A.; Fernández, Rocío del Valle; Stellas, Dimitris; Hails, Guillermo; Karaliota, Sevasti; Ashley, Gary W.; Felber, Barbara K.; Pavlakis, George N.; Santi, Daniel V. (Frontiers in Immunology, 2024)
Interleukin(IL)-15 agonists hold promise as immunotherapeutics due to their ability to induce the proliferation and expansion of cytotoxic immune cells including natural killer (NK) and CD8 + T cells. However, they generally have short half-lives that necessitate frequent administration to achieve efficacy. To address this limitation, we have developed a half-life extension technology using hydrogel microspheres (MS). Here, the therapeutic is tethered to MSs by a releasable linker with pre-programed cleavage rates. We previously showed the MS conjugate of single-chain IL-15, MS~IL-15, effectively increased the half-life of IL-15 to approximately 1 week and enhanced the pharmacodynamics. We sought to determine whether the same would be true with a MS conjugate of the IL-15 agonist, receptor-linker IL-15 (RLI). We prepared a long acting MS conjugate of RLI, MS~RLI, and compared it to MS~IL-15. MS~RLI exhibited a half-life of 30 h, longer than most IL-15 agonists but shorter than MS~IL-15. The shorter than expected half-life of MS~RLI was shown to be due to target-mediated-disposition caused by an IL-15 induced cytokine sink. MS~RLI resulted in very potent stimulation of NK and CD44 hi CD8 + T cells, but also caused significant injection-site toxicity that may preclude subcutaneous administration. We thus pivoted our efforts towards studying the MS~RLI for long-acting intra-tumoral therapy, where some degree of necrosis might be beneficial. When delivered intra-tumorally, both MS~IL-15 and MS~RLI had modest anti-tumor efficacy, but high anti-metastatic activity. Thus, intra-tumoral MS~RLI and MS~RLI combined with systemic treatment with other agents could provide beneficial antitumor and anti-metastatic effects without the toxic effects of systemic IL-15 agonists. Our findings demonstrate that intra-tumorally administered long-acting IL-15 agonists counter two criticisms of loco-regional therapy: the necessity for frequent injections and the challenge of managing metastases.